Functional biopolymeric materials for active food packaging: the case of monolayer films of thermoplastic starch and olive leaf extract - Sousa, Rita; Silva, José M.; Verano-Naranjo, Lidia; Cejudo-Bastante, Cristina; Facchinatto, William M.; Almeida, Adelaide; Silvestre, Armando J. D.; Freire, Carmen S. R.; Vilela, Carla (Frontiers in Bioengineering and Biotechnology, 2025)
Active packaging materials based on biopolymers and natural additives represent a significant innovation, offering a sustainable solution of packaging combined with multifunctional bioactive properties to extend the shelf-life of food products. In the present study, bioactive films composed of thermoplastic starch (TPS) and an olive leaf extract (OLE) were fabricated via solvent casting. OLE was used in different concentrations, namely 5 and 10 wt.%, and the films were plasticized with glycerol (20 wt.%). The ensuing homogeneous films are translucent (50% < transmittance <80%, opacity <2.3 mm−1) and exhibited a light-green coloration characteristic of OLE. The inclusion of OLE had a positive effect on the mechanical performance (Young’s modulus ≈1.1 GPa), water resistance (water solubility <29% and moisture absorption ≤45%) and thermal stability (up to 200 °C) of the films. Furthermore, the incorporation of OLE in the plasticized TPS films originated materials with UV-blocking properties (transmittance ≤28%) and high antioxidant activity (DPPH scavenging activities of ca. 90%), as well as antibacterial action against a methicillin-resistant Staphylococcus aureus bacterial strain (maximum reduction of ca. 2.6–log [colony-forming units (CFU) mL–1] after 72 h). Lastly, when used to pack sliced pears stored at +4 °C for 7 days, the TPS/OLE-based films effectively delayed browning, mass loss and pH changes. Overall, the incorporation of OLE into plasticized TPS films demonstrates great potential for sustainable active food packaging, offering an approach to preserve the quality and extend the shelf-life of fresh food products.